PENGEMBANGAN MODEL TAM : EXPERTICE DAN INNOVATIVENESS SEBAGAI VARIABEL MODERATOR STUDI PADA PENGGUNAAN E BANKING - Sri Hartini (STIE Perbanas Surabaya, 2011)
This research has purpose to develop a model of TAM (Technology Acceptance Model). It tries to analyze the role of expertise and innovativeness of the consumers in shaping their attitude. It uses the technique of non random sampling that is accidental sampling. Based on such technique, it gains 105 respondents. It shows that the perceive-easy of use of the products bought by the customers has significant influence towards the customers attitude in e-banking industries. Also, when using the moderating variables, the variables of expertise and innovativeness do not have any role significantly in moderating the relationship between perceive easy of use and the customers attitude towards the transaction in e banking. Again, Perceive usefulness is found to have significant influence on the consumers attitude in using the technology. Besides that, the consumer innovativeness and expertise apply to this condition.